The Moderating Role of Digital Supply Chain and Biodiesel Policy on Fuel Supply Chain Performance in the N-PSO Sector - Deasy Rizqiana; Wahyuningsih Santosa; Tri Wulandari Satitidjati Dewayana; Dwi Rima Lestari (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The implementation of Indonesia’s mandatory biodiesel policy has increased the complexity of fuel supply chain management, particularly in the Non-Public Service Obligation (N-PSO) sector, which operates without price subsidy support. This condition requires strong process integration and operational capability to maintain supply chain performance amid policy dynamics and supply risks. This reserach aims to analyze the effect of supply chain integration on fuel supply chain performance in the N-PSO sector, with supply chain capability as a mediating variable and digital supply chain and biodiesel policy as moderating variables. A quantitative approach was employed using primary data collected through a questionnaire survey of several fuel trading companies and their contractors who are acting under the national biodiesel blending mandate in Indonesia. Data were analyzed using PLS-SEM modeling. The results indicate that supply chain integration has a positive and significant effect on supply chain capability and supply chain performance, and supply chain capability mediates this relationship. Digital supply chain is not proven to moderate the effect of supply chain integration on supply chain capability. In addition, biodiesel policy does not moderate the effect of supply chain capability on supply chain performance. These findings indicate that improvements in supply chain performance in the N-PSO sector are mainly driven by internal integration and operational capability rather than by the moderating role of digitalization and policy intervention.